The influence of teacher leadership on students academic burnout in China: potential multiple mediating effects of meeting basic psychological needs - Fang, Anqi (Frontiers in Psychology, 2025)
Teacher leadership has an important influence on students' academic burnout. Based on the theory of self-determination, this paper constructs an analytical framework of “external environmental resources-internal psychological needs satisfaction” to reduce students' academic burnout. Taking senior high school students in China as samples, it explores the potential effect and mechanism of China teachers' leadership on students–academic burnout. The results show that teacher leadership can not only directly and negatively affect students' academic burnout, but also further negatively affect academic burnout through the parallel mediation of learning autonomy, self-efficacy and teacher-student relationship. Also, the teachers' teaching leadership is an important factor affecting students' academic burnout, and the three psychological needs - autonomy, competence and relationship—have independent functional values on students' academic burnout. Therefore, constructing a good teacher's teaching leadership system can meet students' psychological needs of autonomy, competence and relationship, thus helping to reduce students' academic burnout.